An efficient photochemotherapy nanoplatform based on the endogenous biosynthesis of photosensitizer in macrophage-derived extracellular vesicles. (December 2021) - Li, Ruomeng; Gong, Xue; Hong, Chen; Wang, Hong; Chen, Yingying; Tan, Kaiyue; Liu, Xiaoqing; Wang, Fuan
Abstract: Extracellular vesicles (EVs) have been emerged as versatile drug delivery vehicles due to their outstanding biocompatibility and long-term circulation, yet are constrained with low targeting property and inefficient loading capacity from post-synthetic passive EVs encapsulation. Herein, we report a simple and feasible in situ biosynthetic approach to encapsulate tumor-targeting folate (FA)-modified EVs with intracellularly produced protoporphyrin X (PpIX) and doxorubicin (DOX). As compared with the traditional directly drug-incubated or drug-electroporated EVs, these biosynthesized EVs revealed high drug-loading efficiency with minimized structural and functional perturbations. Our multifunctional EVs revealed the enhanced accumulation and penetration into deep tumor parenchyma, as well as the strengthened immune response to ablate orthotopic and metastatic tumors, thus realizing the more reliable photochemotherapy. As an intelligent multi-mode therapeutic system, our biosynthetic EVs could be engineered with more therapeutic agents and show great promise for biomedicine applications.